Digital Signal Processing for Short-Reach Optical Communications: A Review of Current Technologies and Future Trends - Zhong, Kangping; Zhou, Xian; Huo, Jiahao; Yu, Changyuan; Lu, Chao; Lau, Alan Pak Tao (Journal of lightwave technology, 2018)
Driven primarily by cloud service and data-center applications, short-reach optical communication has become a key market segment and growing research area in recent years. Short-reach systems are characterized by direct detection-based receiver configurations and other low-cost and small form factor components that induce transmission impairments unforeseen in their coherent counterparts. Innovative signaling and digital signal processing (DSP) play a pivotal role in enabling these components to realize their ultimate potentials and meet data rate requirements in cost-effective manners. This paper presents an overview of recent DSP developments for short-reach communications systems and discusses future trends.